The Development of Sports Information Management System (SMICO) of KONI Salatiga Municipal (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purposes of the research are: obtaining a product of Sport Information Management System (called SMICO) in KONI Salatiga Municipal, evaluating the effectiveness of SMICO product in KONI Salatiga Municipal, finding out the acceptance of SMICO product in KONI Salatiga Municipal, therefore it is expected that SMICO takes a role in decision making. The method in this research is developed from Borg and Gall procedural model, in which includes: observation, planning, and developing. Data taken is by field observation, questionnaire distribution, data collection and filing. The finding of this research is a software product titled SMICO website based in KONI Salatiga Municipal in which: the percentage of effectiveness test of the home page is 65%, which means it is satisfactory valid, the percentage of the menu page is 60% which means it is valid, the percentage of the menu sports is 61% which means it is good, the score result of the specification of the use is 4.0 or 80% which means it is excellent, the score result of submenu of sport information is 3.2 or 63% which means it is good, the score result of contact submenu is 4.7 or 93% which means it is excellent, the score result of web management and maintenance is 4.1 or 83% which means it is excellent. The result of the athletes as the respondents show that SMICO has average score 4.44 or 88.8% which means that it is excellent, the average score from the coaches as respondents shows 4.31 or 86.18% which means it is excellent.